A High Efficient High Input Power Factor Interleaved Boost Converter - Jayakumar M S; Ajeesh G (International Journal of Electrical and Computer Engineering (IJECE), 2012)
In this paper an improved ZVT interleaved boost PFC topology is introduced. The proposed ZVT interleaved boost converter is composed of two cell boost conversion units and an active auxiliary circuit. The proposed converter has two important advantages over the similar soft switching converters. The first one is that parallel to the main switches of the converter the auxiliary switch also operates under soft switching condition. Providing soft switching conditions for interleaved boost converters with more than one cells using only one auxiliary switch is another advantage of this topology. The prototype for the proposed converter was developed with an input of 110V-220V ac power supply feeding a resistive output load of 600 watts. In addition, the proposed converter has the advantages of fewer structure complications, lower cost and ease of control.DOI:http://dx.doi.org/10.11591/ijece.v2i3.254